WHAT WE SHOULD DO FOR CROUZON SYNDROME ? Poster Presentation - Case Report - Resident - RYAN AQUARI; Linda Trisna; Riani Erna (Majalah Oftalmologi Indonesia, 2023)
Introduction : Crouzon syndrome is a rare genetically disease characterized by craniosynostosis resulting in skull and facial deformities. Fortunately, not all patient requires surgery so we will review the workup of Crouzon syndrome and describes the collaboration of health professionals needed to manage this condition. Case Illustration : A 10 years old boy came to hospital with exophthalmos since birth. There is decreasing of visual acuity on RE caused by atrophy papil and leads to sensoric exotropia. There is also lagophthalmos 1 mm on the both eyes. Brain CT shown there are craniosynostosis and thickening of the rectus muscles. This patient also do a bone Survey with the result are asymmetrical calvarial thickening, cooper beaten skull, shallow orbits, depressed nasal bridge and hypoplasia maxilla. This case is managed by multidisciplinary to correct the maldevelopment of the midface and orbits to prevent blindness, airways obstruction and intellectual disability related. Discussion : The combination of detailed family history, the use of various imaging modalities and genetic testing help differentiate the spectrum of craniosynostosis syndromes. The management is complex and requires a team of subspecialists including pediatricians, oral maxillofacial surgeons, plastic surgeons, neurosurgeons, otorhinolaryngology, and ophthalmologists (pediatric and oculoplastics). Long-term follow up needed to monitor ocular development due to the propensity strabismic amblyopia and atrophy optic. Conclusion : An interprofessional team approach will provide the best outcomes and recognizing possible complications for crouzon syndrome.